2006
DOI: 10.1086/503269
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Primary Immunodeficiency with Specific Natural-Killer Cell Deficiency Maps to the Centromeric Region of Chromosome 8

Abstract: We describe four children with a novel primary immunodeficiency consisting of specific natural-killer (NK) cell deficiency and susceptibility to viral diseases. One child developed an Epstein-Barr virus-driven lymphoproliferative disorder; two others developed severe respiratory illnesses of probable viral etiology. The four patients are related and belong to a large inbred kindred of Irish nomadic descent, which suggests autosomal recessive inheritance of this defect. A genomewide scan identified a single 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
93
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 22 publications
(30 reference statements)
1
93
0
3
Order By: Relevance
“…48 In this syndrome, the combined monocyte and NK-cell deficiency may be permissive for severe HPV disease. 19 The NK-cell deficiency in this disease may also account for the susceptibility to some herpesvirus infections 49,50 and to recurrent fetal losses in patients 1.II.5 and 4.II.1. 51 Viral etiologies have been clearly identified for certain human cancers: HPV with squamous carcinomas 52 ; EBV with nasopharyngeal carcinoma, leiomyosarcomas, and some lymphomas 53 ; and human herpesvirus 8 with Kaposi sarcoma and Castleman disease.…”
Section: Discussionmentioning
confidence: 99%
“…48 In this syndrome, the combined monocyte and NK-cell deficiency may be permissive for severe HPV disease. 19 The NK-cell deficiency in this disease may also account for the susceptibility to some herpesvirus infections 49,50 and to recurrent fetal losses in patients 1.II.5 and 4.II.1. 51 Viral etiologies have been clearly identified for certain human cancers: HPV with squamous carcinomas 52 ; EBV with nasopharyngeal carcinoma, leiomyosarcomas, and some lymphomas 53 ; and human herpesvirus 8 with Kaposi sarcoma and Castleman disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, these cases were sporadic, and the defect in NK cells was documented after clinical viral diseases, raising lymphoproliferative disorder, and two others developed severe respiratory illnesses that were probably of viral origin. We mapped this immunodeficiency to a single 12-Mb region on the centromeric region of chromosome 8 (15) and then tried to decipher the molecular genetic basis of this new syndrome combining selective NK cell deficiency, growth retardation, adrenal insufficiency, and predisposition to viral infections and, possibly, cancer (18).…”
Section: Introductionmentioning
confidence: 99%
“…Their control relies on the integration of multiple signals received via inhibitory receptors mainly binding to MHC class I molecules and activating receptors recognizing ligands primarily expressed on infected or transformed cells. Studies on NK cell deficiencies in humans highlight their pivotal role in the control of herpesvirus infections including human cytomegalovirus (HCMV), herpes simplex virus (HSV), vesicular stomatitis virus (VSV), and EBV (1)(2)(3). A recent case report revealed that NK cells were able to control HCMV infection even in the absence of T cells (4).…”
Section: Introductionmentioning
confidence: 99%